Heritability of Hepatic Fibrosis and Steatosis Based on a Prospective Twin Study - Loomba, Rohit; Schork, Nicholas; Chen, Chi-Hua; Bettencourt, Ricki; Bhatt, Ana; Ang, Brandon; Nguyen, Phirum; Hernandez, Carolyn; Richards, Lisa; Salotti, Joanie; Lin, Steven; Seki, Ekihiro; et al. (Gastroenterology (New York, N.Y. 1943), 2015)
Little is known about the heritability of hepatic fibrosis, and the heritability of hepatic steatosis has not been assessed systematically in adults. We investigated the heritability of hepatic fibrosis and steatosis in a community-dwelling twin cohort. We performed a cross-sectional analysis of a cohort of well-characterized twins residing in Southern California including 60 pairs of twins (42 monozygotic and 18 dizygotic; average age, 45.7 ± 22.1 y; average body mass index, 26.4 ± 5.7 kg/m2). We collected data on medical history, physical examinations, fasting laboratory test results, and liver health; all participants underwent an advanced magnetic resonance imaging (MRI) examination of the liver from January 2012 through January 2015. Hepatic steatosis was quantified noninvasively by MRI and determined based on the proton-density fat fraction (MRI-PDFF); liver fibrosis was measured based on stiffness measured by magnetic resonance elastography. Twenty-six of the 120 subjects (21.7%) had nonalcoholic fatty liver disease (defined as MRI-PDFF ≥ 5% after exclusion of other causes of hepatic steatosis). The presence of hepatic steatosis correlated between monozygotic twins (r2 = 0.70; P < .0001) but not between dizygotic twins (r2 = 0.36; P = .2). The level of liver fibrosis also correlated between monozygotic twins (r2 = 0.48; P < .002) but not between dizygotic twins (r2 = 0.12; P = .7). In multivariable models adjusted for age, sex, and ethnicity, the heritability of hepatic steatosis (based on MRI-PDFF) was 0.52 (95% confidence interval, 0.31–0.73; P < 1.1 × 10–11) and the heritability of hepatic fibrosis (based on liver stiffness) was 0.5 (95% confidence interval, 0.28–0.72; P <6.1 × 10–11). A study of twins provides evidence that hepatic steatosis and hepatic fibrosis are heritable traits.